Analyses the Construction of the Indonesian Ulema Council Fatwa on the Halalness of the Sinovac Covid-19 Vaccine using the Jasser Auda’s Perspective of Islamic Law Development Models - Abduh, Muhammad; Abadi, Khafid; Islamy, Athoillah; Susilo, Adib (Universitas Islam Negeri Raden Intan Lampung, 2021)
The spread of hoax news related to whether it is safe or not and whether or not the use of the Covid-19 vaccine is lawful has created a pro-contra attitude among the Indonesian people towards the Covid-19 vaccination program. For this reason, the Indonesian Ulema Council (MUI) has issued a fatwa to provide legal enlightenment on the halal use of the Covid-19 vaccine. This study examines in depth the construction of the fatwa and identifies the Islamic law development model used in constructing the fatwa. This research is purely philosophical normative and uses the models of Islamic legal development proposed by Jasser Auda. The results of the study conclude that the construction of the MUI fatwa on the halalness of the Sinovac vaccine had used a holistic model of Islamic law. This is indicated by some characteristics inherent in the construction of the fatwa namely : (i) the wholeness and multidimensional character, which is indicated by the use of universal textual arguments ('aam). (ii) the purposive character, which isindicated by the use of various fiqh rules emphasizing the realization of benefit as the basis and orientation of legal determination. (iii) the openness characterwhich is indicated by the acceptance of the health and medical science principles which incidentally is outside the field of Islamic law